Students’ Experiences in Undertaking Nursing Professional Practice During the COVID-19 Pandemic: A Case Study of Strengthening Clinical Adaptation in Taichung City - Lin, Wen-Yuan; Wu, Chien-Chih (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aims to explore in depth the experiences of nursing students in performing professional practice during the COVID-19 pandemic, including the challenges, adaptation strategies, and learning processes that emerged in a hospital setting. Methodology: This study used a qualitative descriptive method with in-depth interviews. Data were collected using semi-structured interview guides, audio-recording tools, and verbatim transcription. Thematic analysis was performed using manual coding supported by Microsoft Word and Microsoft Excel to categorize themes and sub-themes. Main Findings: The study identified three major themes: the use of personal protective equipment, students’ concerns regarding virus transmission, and obstacles encountered during clinical practice. Students reported fear of contracting and transmitting the virus, limited patient interaction, and reduced opportunities for hands-on learning. They developed self-adjustment strategies such as consistent PPE use, maintaining physical immunity, and seeking supervision support. Novelty/Originality of this study: This study offers new insight by capturing the unique clinical learning experiences of nursing students during a global health crisis, emphasizing the intersection between psychological stress, safety compliance, and clinical learning limitations. It contributes new knowledge on how pandemics reshape professional nursing education and highlights the need for adaptive, resilient clinical training models.